Poe the detective the curious circumstances behind The mystery of Marie Roget - Walsh, John Evangelist 1927- (Rutgers Univ. Press, 1968)
Based on "Edgar Allan Poe's bold claim that he had solved a real-life murder mystery without leaving the comfort of his armchair"--Preface.
Keywords: Poe, Edgar Allan -- 1809-1849; Poe, Edgar Allan <1809-1849> -- Mystery of Marie Roget; Poe, Edgar Allan -- 1809-1849 -- The mystery of Marie Rogêt; Detective and mystery stories, American -- History and criticism